2014
DOI: 10.1021/ac4040373
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Single Base-Pair Mismatch Detection via Aggregation of Exonuclease-Sheared Gold Nanoparticles

Abstract: Single nucleotide polymorphism (SNP) detection is important for early diagnosis, clinical prognostics, and disease prevention, and a rapid and sensitive low-cost SNP detection assay would be valuable for resource-limited clinical settings. We present a simple platform that enables sensitive, naked-eye detection of SNPs with minimal reagent and equipment requirements at room temperature within 15 min. SNP detection is performed in a single tube with one set of DNA probe-modified gold nanoparticles (AuNPs), a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…An interesting finding by the authors is that the melting transition is extremely sharp, offering excellent selectivity of fully complementary DNA targets over those with one or more mismatches. 65 On the basis of a similar strategy, biorecognition element modified AuNPs have been successfully employed as colorimetric reporters for glucose, dopamine, glutathione (GSH), adenosine triphosphate (ATP), K + , etc. 16f The controlled loss of surface ligands can also be applied to construct colorimetric bioassays.…”
Section: Aunp-based Lspr Assaysmentioning
confidence: 99%
“…An interesting finding by the authors is that the melting transition is extremely sharp, offering excellent selectivity of fully complementary DNA targets over those with one or more mismatches. 65 On the basis of a similar strategy, biorecognition element modified AuNPs have been successfully employed as colorimetric reporters for glucose, dopamine, glutathione (GSH), adenosine triphosphate (ATP), K + , etc. 16f The controlled loss of surface ligands can also be applied to construct colorimetric bioassays.…”
Section: Aunp-based Lspr Assaysmentioning
confidence: 99%
“…We have previously demonstrated that the apurinic endonuclease activity of Exo III can effectively enable EATR-mediated AuNP aggregation for rapid and sensitive detection of single-base-mismatched DNA. 6 Here, we showed that Exo III’s apurinic endonuclease activity could mediate CBSA-based EATR in solution as well as on particle surface. We thus believe that the highly active and robust apurinic endonuclease activity of Exo III should allow many DNA-based EATR sensor platforms to be applied to our CBSA-based EATR assays for detection of various small-molecule targets.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, a substantial fluorescent signal can be generated by a single copy of the target though EATR, greatly decreasing the limit of detection. 3,5 Given that DNA can be easily modified with various signaling reporters 3,68 and that different nucleases can be utilized to process the target–probe duplex, 3,5,7,9 many EATR-based assays have been developed for DNA detection with ultrahigh sensitivity. 4 …”
mentioning
confidence: 99%
“…Nucleic acid test (NAT) is a technique for diagnosing genotypes by detecting the presence, quantity, and mutation of nucleotide sequences using the Watson‐Crick interaction and DNA replication. NAT can be utilized to detect single‐nucleotide polymorphism (SNP) specifically (Eom et al, ; Wu et al, ) or to detect microRNA (miRNA) using noninvasive sampling (Ge et al, ; Yang et al, ; Ying, Ju, Sun et al, ). Also, pathogens including virus can be detected for the prevention of infectious diseases (Guo et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%